Regulators of Tfh Cell Differentiation - Jogdand, Gajendra M.; Mohanty, Suchitra; Devadas, Satish (Frontiers in Immunology, 2016)
The follicular helper T (Tfh) cells help is critical for activation of B cells, antibody class switching, and germinal center (GC) formation. The Tfh cells are characterized by the expression of CXC chemokine receptor 5 (CXCR5), ICOS, programed death 1 (PD-1), B cell lymphoma 6 (BCL-6), and IL-21. They are involved in clearing infections and are adversely linked with autoimmune diseases and also have a role in viral replication as well as clearance. On the one hand, Tfh cells are generated from naive CD4+ T cells with sequential steps involving cytokine signaling (IL-21, IL-6, IL-12, activin A), migration, and positioning in the GC by CXCR5, surface receptors (ICOS/ICOSL, signaling lymphocyte activation molecule-associated protein/signaling lymphocyte activation molecule) as well as transcription factor (BCL-6, c-Maf, and signal transducer and activator of transcription 3) signaling and repressor miR155. On the other hand, Tfh generation is negatively regulated at specific steps of Tfh generation by specific cytokine (IL-2, IL-7), surface receptor (PD-1, CTLA-4), transcription factors B lymphocyte maturation protein 1, signal transducer and activator of transcription 5, T-bet, KLF-2 signaling, and repressor miR 146a. Interestingly, miR-17–92 and FOXO1 act as a positive as well as a negative regulator of Tfh differentiation depending on the time of expression and disease specificity. Tfh cells are also generated from the conversion of other effector T cells as exemplified by Th1 cells converting into Tfh during viral infection. The mechanistic details of effector T cells conversion into Tfh are yet to be clear. To manipulate Tfh cells for therapeutic implication and or for effective vaccination strategies, it is important to know positive and negative regulators of Tfh generation. Hence, in this review, we have highlighted and interlinked molecular signaling from cytokines, surface receptors, transcription factors, ubiquitin ligase, and microRNA as positive and negative regulators for Tfh differentiation.